CSF Leak Following COVID-19 Swab: A Case Report and Literature Review - Mansour, Laure Taher; Ovenden, Christopher; Patel, Sandy; Abou-Hamden, Amal; Psaltis, Alkis (WFNS Journal, 2025)
Millions of nasopharyngeal swabs have been performed during the COVID-19 pandemic. Although generally considered a safe diagnostic test, rare adverse events have been reported. We describe a case of cerebrospinal fluid (CSF) leak in an otherwise well woman. A literature search of Pubmed and Ovid Embase was also performed, with the aim of identifying all reported cases of CSF leak following COVID-19 swabs. Extracted data points included demographics, pre-existing risk factors, past trauma, site of injury, meningitis, and management. This case report concerns a 54-year-old woman with no known risk factors. She had 10 nasopharyngeal swabs performed. Three days following the last swab, she developed persistent rhinorrhea. CTB demonstrated focal defect in the left lamella and cribriform plate, with associated soft tissue prominence. An MRI identified a meningocele arising from the left side of the cribriform plate. The patient underwent endoscopic repair without complications. A total of 17 reported cases of CSF leak following a COVID-19 swab were identified. Majority of the patients were female (65%), and most did not have any risk factors. Four patients had a preexisting skull base deformity and three had benign intracranial hypertension. The most common site of injury was the cribriform plate (11/17). Four cases were complicated by meningitis. Most patients were surgically managed with endoscopic repair while the remaining three patients were successfully managed conservatively. CSF leaks following nasopharyngeal swabs are rare but need to be promptly identified by clinicians, even in patients without known pre-existing risk factors.
Keywords: CSF leak; nasopharyngeal swab; COVID-19; case report